UNSUR FISIK DAN BATIN PUISI PERAHU KARYA HAMZAH FANSURI DAN SYAIR LA RABBA SIWAKA KARYA ABU AL-‘ATIYAH - Sumarni (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This research aims to reveal the similarities and differences containsed in Hamzah Fansuri's poem "Perahu" and the poem "La rabba siwaka" by Abu Al-'Atiyah by using comparative literary theory. The approach used is structural, that is, what is compared in the two poems are the intrinsic elements that build the poetry, and these elements are the inner elements and the physical elements. The method used is a descriptive qualitatsive method with data collection techniques in the form of note-taking techniques. The data sources from the two poems were analyzed and then compared with the mental and physical elements. The results of this research found similarities between boat poetry and Abu Al-'Atiyah's poetry in terms of theme, tone, use of concrete words, rhyme and typography. Then the differences were also found in terms of theme, taste, message, diction, imagery, rhyme and figure of speech.